Development of Islamic Sharia-Based Curriculum in Islamic Universities in Aceh: A Study on the Implementation of Aceh Qanun Number 9 of 2015 - Sulaiman Sulaiman; Siti Yusnaini; Anton Widyanto (Universitas Islam Negeri Mataram, 2023)
This study aims to examine the implementation of an Islamic Sharia-Based Curriculum (KBSI) at Islamic Colleges (PTKI) in Aceh. This qualitative study used the purposive sampling method to select the participants, including five college leaders and 50 lecturers from UIN Ar-Raniry, IAIN Lhokseumawe, University of Muhammadiyah Aceh, STIS Al-Hilal Sigli, and STAI Teungku Chik Pante Kulu. The data were collected through interviews, observation, and documentation. The research shows that the strategy for developing an Islamic Sharia-based Curriculum (KBSI) at PTKI in Aceh is conducted by an integrated model, separated subject curriculum and correlated curriculum. The policy for developing an Islamic sharia-based curriculum at PTKI in Aceh refers to philosophical, sociological, historical, and juridical foundations in the form of Aceh qanuns. It further finds that the development of an Islamic sharia-based curriculum at PTKI in Aceh is an effort to guide the young Acehnese generations who are sharia-compliant and tolerant using special autonomy opportunities. Meanwhile, the difficulties in developing this curriculum are due to Aceh's internal and external PTKI factors. The obstacles are due to internal factors where PTKI leaders do not respond to the opportunities for KBSI reconstruction. On the other hand, obstacles also deal with external factors where collaboration between PTKI and the Aceh government in the context of KBSI reconstruction is less optimal.